2019
DOI: 10.1128/iai.00158-19
|View full text |Cite
|
Sign up to set email alerts
|

CD4+T Cell Regulation of Antibodies Cross-Reactive with Fungal Cell Wall-Associated Carbohydrates afterPneumocystis murinaInfection

Abstract: Pneumocystis pneumonia is a life-threatening opportunistic fungal infection observed in individuals with severe immunodeficiencies, such as AIDS. Molecules with the ability to bind β-glucan and signal at Fcγ receptors enhance defense against Pneumocystis f. sp. murina, though it is unclear whether antibodies reactive with fungal cell wall carbohydrates are induced during Pneumocystis infection. We observed that systemic and lung mucosal immunoglobulins cross-reactive with β-glucan and chitosan/chitin are gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Previous work has shown that conserved natural IgM antibodies with carbohydrate specificities can mediate innate and adaptive immunity against Pneumocystis (11,12). Given that Pneumocystis clearance is mediated by class II restricted CD4+ T cells, we hypothesized that IgM with protein specificities may predict subsequent class II dependent antigens.…”
Section: Baseline Anti-pneumocystis Igm Titers In C57bl/6 Micementioning
confidence: 99%
“…Previous work has shown that conserved natural IgM antibodies with carbohydrate specificities can mediate innate and adaptive immunity against Pneumocystis (11,12). Given that Pneumocystis clearance is mediated by class II restricted CD4+ T cells, we hypothesized that IgM with protein specificities may predict subsequent class II dependent antigens.…”
Section: Baseline Anti-pneumocystis Igm Titers In C57bl/6 Micementioning
confidence: 99%
“…Moreover, despite CD4+ T-cell depletion, IgM levels increased significantly. Thus, an immune response against Pneumocystis β-glucan might occur under conditions of CD4+ T cell-related immunodeficiency via differential CD4+ T cell-dependent regulation of mucosal antibody responses ( 50 ).…”
Section: β-Glucan Mediated Initial Immunitymentioning
confidence: 99%